Quality of Education and Marketability against Career Readiness: A TVET Students’ Perspective - Majid, Zuber Abd; Hussin, Muhammad; Norman , Helmi; Zulnaidi, Hutkemri (International Journal of Psychosocial Rehabilitation, 2020)
The ability to empower an economy requires more than just information. Given the goal of achieving long-term stability, Malaysia will require technical and vocational education training (TVET) qualifications from its human resources. Meanwhile, educational institutions will be challenged to produce knowledgeable human resources with the skills needed to face the ever-changing work environments. This study aims to identify the relationship between the quality of educational service, marketability skills and career readiness among TVET students. Data were collected from a cross-sectional survey of 448 final year TVET students at a public university and were examined using a stratified sampling method. The findings reveal a positive significant correlation between the quality of educational service, marketability skills and career readiness. The implication of this study is that students are prepared and aware of the need for career development skills. Value-added skills make students marketable and are dominant indicators of increasing student career readiness.